Studi Komparatif Penggunaan Aplikasi Scratch dan Aplikasi Blockly pada Mata Pelajaran Informatika Siswa SD Islam Al-Azhar 32 Padang - Sukri, Indah Hasanah; Amilia, Winanda; Yeni, Fetri; Rahmayanti , Elsa (Indo-MathEdu Intellectuals Journal, 2024)
This research is motivated by the implementation of Informatics learning at SD Islam Al-Azhar 32 Padang. The theory and practice of programming languages ​​is included in the Informatics material but is not implemented so that the ability to recognize and understand programming languages ​​in children has not yet emerged. Apart from that, the Informatics learning outcomes of students who have not yet reached the KKM are 70. This research aims to determine the effect of the scratch programming language in improving the Informatics learning outcomes of class IV students at Al-Azhar 32 Islamic Elementary School in Padang. This type of research is quantitative research. This quantitative research uses experimental methods. As for several types of experimental methods, researchers used Quasi Experiments. Then, the research design pattern used in this research uses the non-equivalent group design. The non-equivalent group design is a design that requires the existence of an experimental and control group. This is because the determination of the hypothesis is based on the results of the observations of the two groups. Determination of experimental and control groups is not random. These two groups will later be tested using the same instruments and analyzing which treatment is more optimal